Chicken Bone Based Adsorbent for Adsorption of Pb(II), Cd(II), and Hg(II) Metals Ion Liquid Waste - Uswatun Hasanah; Ani Iryani; Agus Taufiq; Dimas Apryandi Darma Putra (Universitas Pakuan, 2021)
High productivity of chicken meat for supplying society also make some impact in high productivity of chicken bone and because it’s unraveling properties makes this become waste. Pharmaceutical’s Waste comes from production process, adstertion of production tools, laboratory activities and rejected product. Laboratory’s routine analysis also producing residual waste analysis, one of the source is come from heavy metals analysis of Pb, Cd, dan Hg. General process for waste treatment producing high quantity of sludge, mean while using third party service have impact in high costing of transportation and treatment process. An alternatif way for this case is using sorption treatment. Initial research starts from preparation of chicken bone-based adsorbent and its characterization using SEM and FTIR, followed by quality analysis of fresh waste (which is waste A and waste B) observed at pH, COD, TDS, TSS also Pb, Cd, dan Hg metals. Adsorption process was observed from adsorbent’s graying temperature, adsorbent’s particle size, contact time, pH of waste, and adsorbent’s weight. Best result from adsorption process were applicated at fresh waste and simulation waste of Pb, Cd, and Hg metals also re-testing quality analysis of fresh waste and simulation waste for before-after result comparing purpose. The purpose of this research is for characterizing chicken bone-based adsorbent, observing adsorption process of Characterization of chicken bone ash based adsorbent has been carried out in adsorbing Pb, Cd, and Hg metals in pharmaceutical laboratory waste. Functional group analysis with Fourier Transform Infrared Spectrophotometer (FTIR) showed that the chicken bone ash adsorbent contained the mineral compound apatite carbonate. Surface morphology with a Scanning Electron Microscope (SEM) shows that the adsorbent surface is porous and appears to be adsorbing metals. From the adsorption observations, it was found that the best adsorption conditions were at an ashing temperature of 800 oC, particle size of 80 mesh, contact time of 30 minutes, waste conditions at pH 6 and an adsorbent weight of 600 mg. Application chicken bone-based adsorbent against pharmaceutical waste shows its existence improve the quality of waste but still do not meet the quality standard requirements for Hg metal.